Adjuvant Therapy for Renal Cell Carcinoma: Past, Present, and Future - Pal, Sumanta K. (AlphaMed Press, 2014)
At the present time, the standard of care for patients who have received nephrectomy for localized renal cell carcinoma (RCC) is radiographic surveillance. With a number of novel targeted agents showing activity in the setting of metastatic RCC, there has been great interest in exploring the potential of the same agents in the adjuvant setting. Herein, we discuss the evolution of adjuvant trials in RCC, spanning from the immunotherapy era to the targeted therapy era. Pitfalls of current studies are addressed to provide a context for interpreting forthcoming results. Finally, we outline avenues to incorporate promising investigational agents, such as PD-1 (programmed death-1) inhibitors and MNNG transforming gene inhibitors, in future adjuvant trials.